Research on the influencing factors and realization path of Chinese residents’ health levels: a social, ecological, and medical perspective - Hongwei Li; Ruixin Wang; Hongliang Wang (BMC Public Health)
Abstract Background The health of the population serves as a cornerstone for sustainable economic development and stands as a vital indicator of national prosperity and strength. Based on the theory of health human capital, this study explores the practical issues of enhancing residents' health levels through the synergy of social, ecological, and medical factors. Methods Utilizing provincial panel data from China spanning 2011 to 2020, this research employs entropy methods and dynamic Qualitative Comparative Analysis (QCA) to measure the health levels of Chinese residents. The study analyzes the synergistic roles of social, ecological, and medical factors in improving health from both a temporal perspective and a configurational viewpoint. Results No single factor is a necessary condition for achieving high health levels among residents. However, the necessity of per capita health expenditure has been increasing yearly, showing a temporal effect. There are four distinct pathways that can lead to high health levels, which can be further categorized into social-ecological-medical synergistic, social-ecological, and social-medical driven configurations. Temporally, the consistency of configurations 1 and 3 collectively decreased in 2020, likely due to the outbreak of COVID-19, which temporarily shifted the core factors affecting residents' health. Spatially, there are no significant regional effects among the four configurations, indicating that their explanatory power does not significantly differ across provinces. Conclusions The collaborative efforts of social, ecological, and medical factors are found to significantly enhance the health levels of residents in China. Drawing on existing research in the field of public health, the study proposes an analytical framework for understanding the factors influencing health levels. By integrating a configurational perspective into the study of health human capital theory, this research broadens the analytical lens used to examine health levels, offering important theoretical insights and policy implications.